Aluminum alloy negative electrode material for high-capacity lithium ion battery and preparation process of aluminum alloy negative electrode material

By optimizing the preparation process of aluminum alloy negative electrode materials, including reasonable proportional alloy elements and nano-scale powder preparation, the instability problem caused by volume expansion of aluminum alloy materials in lithium-ion batteries is solved, and high capacity, long life and low cost battery performance is achieved.

CN119852355APending Publication Date: 2025-04-18INNER MONGOLIA LIANSHENG NEW ENERGY MATERIALS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411955913.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-28
Publication Date
2025-04-18

AI Technical Summary

Technical Problem

The existing lithium-ion battery anode materials have limitations in terms of energy density, safety and cost, especially aluminum alloy materials are prone to volume expansion during the lithium-ion embedding and deintercalation process, resulting in unstable electrode structure.

Method used

The optimized aluminum alloy negative electrode material preparation process is adopted, including raw material preparation, smelting, casting, solid solution, annealing, microscopy treatment and surface modification. Nano-scale aluminum alloy powder is formed by reasonably proportioning alloy elements such as magnesium, silicon, zinc, and copper, and using high-energy ball milling and surface carbon coating.

Benefits of technology

It significantly improves the electrochemical performance of the material. The first discharge specific capacity of the negative electrode material can reach 250-300mAh/g, and the capacity retention rate exceeds 90% after 500 cycles. At the same time, the cycle life of lithium-ion batteries is extended, making it suitable for large-scale industrial production.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention provides an aluminum alloy negative electrode material for a high-capacity lithium ion battery and a preparation process of the aluminum alloy negative electrode material. According to the aluminum alloy negative electrode material, aluminum serves as a matrix, alloying elements such as magnesium, silicon, zinc and copper are added, and the negative electrode material is prepared through the following processes of raw material preparation, smelting, rapid cooling casting forming, solid solution treatment, annealing treatment, microcosmic treatment and high-energy ball milling, the particle size of powder ranges from 50 nm to 200 nm, and surface coating modification is conducted; the calcination temperature is 400-500 DEG C; the prepared aluminum alloy negative electrode material has high specific capacity, high cycle stability, excellent conductivity and long cycle life, the first discharge specific capacity can reach 250-300 mAh / g, the capacity retention ratio after 500 cycles is larger than or equal to 90%, and the aluminum alloy negative electrode material is suitable for being applied to a negative electrode of a high-capacity lithium ion battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a preparation process of a battery negative electrode material, and more specifically to an aluminum alloy negative electrode material for a high-capacity lithium-ion battery and a preparation process thereof. Background Art

[0002] Lithium-ion batteries have been widely used in portable electronic devices, electric vehicles, and energy storage systems due to their high energy density, long cycle life, and low self-discharge rate. However, as people's demand for battery capacity and performance continues to increase, the limitations of existing negative electrode materials in terms of energy density, safety, and cost have gradually emerged. Therefore, the development of new negative electrode materials with high capacity and stable performance has become one of the key directions of lithium-ion battery research.

[0003] Aluminum alloys have attracted widespread attention in recent years due to their low density, high specific strength, good corrosion resistance and abundant resources. Aluminum and its alloys have potential advantages as negative electrode materials for lithium-ion batteries, especially their high theoretical specific capacity and excellent electrical conductivity, which can significantly improve the overall performance of the battery. However, since aluminum is prone to volume expansion during the insertion and extraction of lithium ions, resulting in instability of the electrode structure, this has seriously restricted its development in practical applications.

[0004] Therefore, the development of a new type of aluminum alloy negative electrode material and its optimized preparation process are of great significance for achieving performance improvement of high-capacity lithium-ion batteries. Summary of the invention

[0005] In view of the above technical problems, the present invention proposes an aluminum alloy negative electrode material for high-capacity lithium-ion batteries and its preparation process, aiming to solve the bottleneck problem in the prior art through innovative material design and process optimization, and provide a new option with high capacity, high stability and low cost for the lithium-ion battery field. The specific scheme is as follows:

[0006] A preparation process of an aluminum alloy negative electrode material for a high-capacity lithium-ion battery, the preparation process comprising the following steps:

[0007] S1. Raw material preparation: aluminum is used as the matrix, and magnesium, silicon, zinc and copper are added;

[0008] S2. Melting: Melting is carried out in a melting furnace: the temperature is set at 700℃-750℃; inert gas protection is used to prevent oxidation; aluminum ingots, magnesium, silicon, zinc and copper are added in the order of proportion and fully stirred;

[0009] S3, casting: the smelted alloy liquid is cast by rapid cooling: the mold temperature is controlled at 200℃-250℃; the cooling rate is controlled at 50℃ / s-100℃ / s;

[0010] S4, solid solution: temperature: 500℃-550℃; holding time: 6-10 hours; cooling method adopts rapid quenching;

[0011] S5, Annealing: Annealing temperature: 250℃-300℃; Holding time: 2-4 hours; Cooling method: furnace slow cooling or air cooling;

[0012] S6. Micro-processing: Use high-energy ball milling to prepare nano-granulated aluminum alloy powder:

[0013] S7, surface modification: surface coating of nanoparticles;

[0014] S8. Prepare negative electrode materials.

[0015] Furthermore, the melt in S2 is stirred by mechanical stirring or electromagnetic stirring at a speed of 200 to 300 rpm for 20 to 30 minutes to ensure uniform distribution of alloy elements.

[0016] Furthermore, during S4 cooling, the cooling medium is water or oil, and the cooling rate is ≥100°C / s.

[0017] Furthermore, the ball milling equipment in S6 is: high-energy planetary ball mill; ball-to-material ratio: 10:1; ball milling time: 12-24 hours; ball milling medium: ethanol or ethylene glycol to avoid oxidation; final powder particle size: 50-200nm.

[0018] Furthermore, the parameters of S7 surface modification are as follows: coating material: carbon material or metal oxide; coating method: solution coating method; preparing a coating material solution with a concentration of 10%; mixing the aluminum alloy powder with the coating solution and ultrasonically dispersing it for 30 minutes; and calcining at 400°C-500°C for 2 hours after drying.

[0019] Furthermore, the carbon material includes conductive graphite or graphene; the metal oxide includes TiO2 or Al2O3.

[0020] Further, a process for preparing an aluminum alloy negative electrode material for a high-capacity lithium-ion battery, S8 comprises the following steps:

[0021] S801: Mixing the treated aluminum alloy powder with a conductive agent and a binder to prepare a negative electrode slurry;

[0022] S802: According to the following ratios: aluminum alloy powder: 80%; conductive agent: 10%; binder: 10%; the slurry is coated on the aluminum foil current collector, and after drying, it is pressed into a sheet to prepare an electrode sheet;

[0023] S803: coating thickness: 50-100μm; tableting density: 2.5-3.0g / cm 3; Drying temperature: 120℃-150℃.

[0024] An aluminum alloy negative electrode material for a high-capacity lithium-ion battery, the negative electrode material comprising the following alloy components in mass percentage: Al: 80%-90%; Mg: 3%-8%; Si: 2%-5%; Zn: 1%-3%; Cu: 1%-2%; the rest being unavoidable impurities.

[0025] Beneficial effects:

[0026] The present invention provides an aluminum alloy negative electrode material for a high-capacity lithium-ion battery and a preparation process thereof, which has the following beneficial effects compared with the prior art:

[0027] (1) By optimizing the aluminum alloy composition, including the optimal ratio of alloying elements such as magnesium, silicon, zinc, and copper, the electrochemical performance of the material is significantly improved. The initial discharge capacity of the negative electrode material can reach 250-300mAh / g, and the capacity retention rate exceeds 90% after 500 cycles. At the same time, by adding alloying elements such as magnesium and copper and surface carbon coating modification, the conductivity of the material is greatly enhanced, which effectively improves the rate performance of lithium-ion batteries. Under high-rate discharge conditions, the negative electrode material can still maintain a high capacity.

[0028] (2) The surface coating process provides the material with higher interface stability, which reduces the mechanical stress caused by volume expansion during charging and discharging, thereby extending the cycle life of lithium-ion batteries.

[0029] (3) The optimized melting, rapid cooling, solution treatment, annealing and nanostructuring process steps are used to effectively control the microstructure of the aluminum alloy material, improve the repeatability and stability of the preparation process, and make it suitable for large-scale industrial production. DETAILED DESCRIPTION

[0030] In order to deepen the understanding of the present invention, the present invention will be further described in detail below in conjunction with examples. The examples are only used to explain the present invention and do not constitute a limitation on the protection scope of the present invention.

[0031] Embodiment 1:

[0032] Raw material preparation

[0033] Aluminum ingot (purity ≥ 99.99%): 80wt%;

[0034] Magnesium ingot: 5wt%;

[0035] Silicon powder: 5wt%;

[0036] Zinc powder: 3wt%;

[0037] Copper powder: 2wt%.

[0038] All raw materials were weighed and then pickled to remove surface impurities.

[0039] S1 Smelting

[0040] The aluminum ingot was placed in a medium frequency induction melting furnace, the temperature was set to 740°C, and argon was introduced as a protective gas.

[0041] After the aluminum ingot is completely melted, magnesium ingot, silicon powder, zinc powder and copper powder are added in sequence, keeping the temperature constant at 740℃.

[0042] Melt stirring: Mechanical stirring was used at a speed of 250 rpm for 25 minutes to ensure uniform distribution of alloying elements.

[0043] S2 Casting

[0044] The smelted alloy liquid is quickly poured into the casting mold, and the casting mold preheating temperature is 230℃.

[0045] A forced cooling method is adopted with a cooling rate of 80°C / s to obtain a casting alloy block, and the alloy grain size is refined.

[0046] S3 solution treatment

[0047] The casting block was placed in a box furnace, the solution temperature was set to 520°C, and the holding time was 8 hours.

[0048] After holding, the alloy is quickly quenched into water with a cooling rate ≥150℃ / s.

[0049] S4 annealing

[0050] The annealing temperature is 280°C and the holding time is 3 hours.

[0051] After annealing, the steel is cooled to room temperature by slow cooling in the furnace to reduce internal stress.

[0052] S5 micro-processing

[0053] The annealed alloy block is ball milled using a high-energy planetary ball mill:

[0054] Ball-to-material ratio: 10:1;

[0055] Ball milling time: 16 hours;

[0056] The ball milling medium was ethanol;

[0057] After ball milling, nano-scale aluminum alloy powder with an average particle size of 80 nm was obtained.

[0058] S6 surface modification

[0059] The nano-aluminum alloy powder is placed in a solution coating device, and a 10% graphene solution is used as a coating material.

[0060] The powder was mixed with the solution and dispersed by ultrasonic for 30 minutes and then dried.

[0061] The dried powder was calcined in a calcining furnace at 450°C for 2 hours to form a uniform carbon coating layer.

[0062] S7 negative electrode material preparation

[0063] The treated aluminum alloy powder was mixed with conductive carbon black and PVDF binder in a mass ratio of 80:10:10, and NMP solvent was added to prepare slurry.

[0064] The slurry was coated on aluminum foil with a coating thickness of 80 μm;

[0065] After drying at 140°C for 12 hours, the tablets were pressed and the density was controlled at 2.8 g / cm 3 , and obtain the finished negative electrode sheet.

[0066] Example 2: Optimized aluminum alloy negative electrode material preparation process

[0067] Raw material preparation

[0068] Aluminum ingot: 85wt%;

[0069] Magnesium ingot: 3wt%;

[0070] Silicon powder: 4wt%;

[0071] Zinc powder: 2wt%;

[0072] Copper powder: 1wt%.

[0073] All raw materials are pickled and dried for later use.

[0074] S1 Smelting

[0075] In an induction melting furnace, the temperature is set at 730°C and the aluminum ingot is placed in the furnace to melt;

[0076] Add magnesium ingot, silicon powder, zinc powder and copper powder in sequence, keeping the temperature constant;

[0077] Melt stirring: electromagnetic stirring was used with a rotation speed of 220 rpm and a stirring time of 30 minutes.

[0078] S2 Casting

[0079] The molten alloy liquid is quickly poured into a 200°C casting mold.

[0080] The cooling rate is 100°C / s, and an alloy ingot is obtained, and the grains in the microstructure are refined and uniform.

[0081] S3 solution treatment

[0082] The temperature was set at 540°C and the holding time was 6 hours.

[0083] The quenching medium is oil, and the cooling rate is ≥120℃ / s.

[0084] S4 annealing

[0085] The annealing temperature was set at 270°C, kept at this temperature for 2 hours, and then cooled to room temperature by air.

[0086] S5 micro-processing

[0087] Ball milling equipment: high energy planetary ball mill;

[0088] Ball-to-material ratio: 10:1;

[0089] Ball milling time: 24 hours;

[0090] The ball milling medium is ethylene glycol;

[0091] Finally, aluminum alloy powder with a particle size of 50 nm was obtained.

[0092] S6 surface modification

[0093] The coating material is titanium dioxide (TiO2), and a 10% concentration TiO2 solution is used.

[0094] After the powder was mixed with the solution, it was dispersed by ultrasonic for 30 minutes, dried and calcined at 400°C for 2 hours to form a uniform oxide coating layer.

[0095] S7 negative electrode material preparation

[0096] The aluminum alloy powder is mixed with the conductive agent and the PVDF binder in a ratio of 80:10:10;

[0097] The coating thickness is 70 μm, the drying temperature is 130°C, and the tablet density is 2.6 g / cm 3 .

[0098] Example 3: Preparation process of aluminum alloy negative electrode material with improved performance

[0099] Raw material preparation

[0100] Aluminum ingot: 90wt%;

[0101] Magnesium ingot: 4wt%;

[0102] Silicon powder: 3wt%;

[0103] Zinc powder: 2wt%;

[0104] Copper powder: 1wt%.

[0105] All raw materials are pre-treated (pickling and drying) before use.

[0106] S1 Smelting

[0107] Place the aluminum ingot into the melting furnace and set the temperature to 750°C;

[0108] Magnesium, silicon, zinc and copper are added in sequence, and the temperature is maintained at 750°C;

[0109] Stirring method: mechanical stirring, the speed is 300rpm, and the stirring time is 20 minutes.

[0110] S2 Casting

[0111] Pour the melt into a casting mold preheated to 250°C;

[0112] The cooling rate was controlled at 60°C / s to obtain an ingot.

[0113] S3 solution treatment

[0114] The temperature is 500°C and the holding time is 10 hours;

[0115] The quenching medium is water, and the cooling rate is ≥150℃ / s.

[0116] S4 annealing

[0117] The annealing temperature is 300°C and the holding time is 4 hours;

[0118] The cooling method is slow cooling along with the furnace.

[0119] S5 micro-processing

[0120] Ball milling equipment: high energy planetary ball mill;

[0121] Ball-to-material ratio: 10:1;

[0122] The ball milling time was 12 h, and the medium was ethanol;

[0123] Finally, aluminum alloy powder with a particle size of 100 nm was obtained.

[0124] S6 surface modification

[0125] The coating material is conductive graphite, and the solution concentration is 10%;

[0126] Ultrasonic dispersion was performed for 30 minutes, and then the mixture was dried and calcined at 500°C for 2 hours.

[0127] S7 negative electrode material preparation

[0128] The aluminum alloy powder is mixed with a conductive agent and a binder in a ratio of 80:10:10;

[0129] The coating thickness is 100 μm, the drying temperature is 150°C, and the tablet density is 2.9 g / cm 3 .

[0130] As a further improvement, the above is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A process for preparing an aluminum alloy negative electrode material for a high-capacity lithium-ion battery, characterized in that: The preparation process comprises the following steps: S1. Raw material preparation: aluminum is used as the matrix, and magnesium, silicon, zinc and copper are added; S2. Melting: Melting is carried out in a melting furnace: the temperature is set at 700℃-750℃; inert gas protection is used to prevent oxidation; aluminum ingots, magnesium, silicon, zinc and copper are added in the order of proportion and fully stirred; S3, casting: the smelted alloy liquid is cast by rapid cooling: the mold temperature is controlled at 200℃-250℃; the cooling rate is controlled at 50℃ / s-100℃ / s; S4, solid solution: temperature: 500℃-550℃; holding time: 6-10 hours; cooling method adopts rapid quenching; S5, Annealing: Annealing temperature: 250℃-300℃; Holding time: 2-4 hours; Cooling method: furnace slow cooling or air cooling; S6. Micro-processing: Use high-energy ball milling to prepare nano-granulated aluminum alloy powder: S7, surface modification: surface coating of nanoparticles; S8. Prepare negative electrode materials.

2. The process for preparing an aluminum alloy negative electrode material for a high-capacity lithium-ion battery according to claim 1, characterized in that: Melt stirring in S2: mechanical stirring or electromagnetic stirring is adopted, the speed is 200-300 rpm, and the duration is 20-30 minutes to ensure uniform distribution of alloy elements.

3. The process for preparing an aluminum alloy negative electrode material for a high-capacity lithium-ion battery according to claim 1, characterized in that: During S4 cooling, the cooling medium is water or oil, and the cooling rate is ≥100℃ / s.

4. The process for preparing an aluminum alloy negative electrode material for a high-capacity lithium-ion battery according to claim 1, characterized in that: S6 medium ball milling equipment: high energy planetary ball mill; ball-to-material ratio: 10:1; ball milling time: 12-24 hours; ball milling medium: ethanol or ethylene glycol, to avoid oxidation; final powder particle size: 50-200nm.

5. The process for preparing an aluminum alloy negative electrode material for a high-capacity lithium-ion battery according to claim 1, characterized in that: The parameters of S7 surface modification are as follows: coating material: carbon material or metal oxide; coating method: solution coating method; prepare a coating material solution with a concentration of 10%; mix the aluminum alloy powder with the coating solution and ultrasonically disperse it for 30 minutes; after drying, calcine at 400°C-500°C for 2 hours.

6. The process for preparing an aluminum alloy negative electrode material for a high-capacity lithium-ion battery according to claim 5, characterized in that: The carbon material includes conductive graphite or graphene; the metal oxide includes TiO2 or Al2O3.

7. The process for preparing an aluminum alloy negative electrode material for a high-capacity lithium-ion battery according to claim 1, characterized in that: S8 includes the following steps: S801: Mixing the treated aluminum alloy powder with a conductive agent and a binder to prepare a negative electrode slurry; S802: According to the following ratios: aluminum alloy powder: 80%; conductive agent: 10%; binder: 10%; the slurry is coated on the aluminum foil current collector, and after drying, it is pressed into a sheet to prepare an electrode sheet; S803: coating thickness: 50-100μm; tableting density: 2.5-3.0g / cm 3 ; Drying temperature: 120℃-150℃.

8. An aluminum alloy negative electrode material for a high-capacity lithium-ion battery, characterized in that: The negative electrode material comprises the following alloy components in weight percentage: Al: 80%-90%; Mg: 3%-8%; Si: 2%-5%; Zn: 1%-3%; Cu: 1%-2%; the rest are inevitable impurities.